Wenshen Yangxue decoction improves endometrial receptivity recovery and promotes endometrial angiogenesis in a rat model - Mingwei Xin; Junqin He; Wei Yang; Xiaodan Yin; Jingshang Wang (Taylor & Francis Group, 2018)
Context: Wenshen Yangxue decoction (WSYXD) is a famous traditional Chinese medicine (TCM) formula and has been used in infertility treatment, but the exact mechanism is still unknown. Objectives: To determine if WSYXD improves endometrial receptivity recovery and promotes endometrial angiogenesis in a rat model. Materials and methods: A total of 100 proestrus female SPF Wistar rats were randomly assigned into five groups: control (saline), model (saline and hydroxyurea solution), high (5.2/100 g), middle (2.6/100 g) and low (1.3/100 g) WSYXD dose groups for 10 d. The microvessel densities, endometrial microstructure, as well as blastocysts number, were observed, followed by detection of angiogenesis-related gene/protein expression by immunohistochemistry, western blot and quantitative real-time polymerase chain reaction (RT-PCR), respectively. Results: Compared with the model group, the blastocyst number in WSYXD middle and high groups were significantly increased (4.50 ± 3.11 vs. 13.00 ± 2.12, 14.00 ± 1.83, p < 0.01). Lower MVD can be found in the model group (4.7) when compared with the normal control (13.7), middle (8.4) and high (9.7) dose groups. Additionally, significant differences were observed in VEGF, HIF-1α, p-AKT, p-PI3K, Ang1 and Ang2 (all p < 0.01) among different groups. Discussion and conclusions: In conclusion, WSYXD could help endometrial receptivity recovery and promote endometrial angiogenesis through PI3K, HIF-1α signalling and VEGF expression regulation. This study provides molecular evidence for application of WSYXD in the clinic and promotes new drug development from TCM.